International regulations for seaports and maritime transport – follow-up 2020 - Vesa Kilpi (Hazard Project, 2022)
EU and IMO (International Maritime Organization) have both issued an extensive body of regulations and standards concerning the shipping of dangerous goods and the prevention of accidents of all sorts.
A previous HAZARD publication by Torstensson & Ekwall (2018) provides an overview of the international rules and regulations related to security and safety in seaports. The report at hand is a status follow-up concerning new regulations since the 2018 study.
In both reports, IMO MSC (Maritime Safety Committee) and MEPC (Marine Environmental Protection Committee) meeting documents and resolution data were gathered from IMO Docs and summarized. The EU directives and regulations concerning seaport safety and security were collected from the EUR-Lex database.
The documentation body is large and diverse, and the lists reported here are not complete but provide a key for the instructions that are more detailed and most up-to-date documents from IMO and EU databases.